Prognosis according to histochemical analysis of liver metastases removed at liver resection. Issue 13 (21st October 2014) - Brunner, S. M.; Kesselring, R.; Rubner, C.; Martin, M.; Jeiter, T.; Boerner, T.; Ruemmele, P.; Schlitt, H. J.; Fichtner‐Feigl, S.
<x xml:space="preserve">Abstract</x> Background Liver metastases occur in 40–50 per cent of patients with colorectal cancer and determine long‐term survival. The aim of this study was to examine the immunological architecture of colorectal liver metastases and its impact on patient survival. Methods Specimens from patients with colorectal liver metastases were stained with haematoxylin and eosin and Masson trichrome, immunostained for α‐smooth muscle actin, CD4, CD45RO and CD8, and analysed by flow cytometry. In addition to histomorphological evaluation, immunohistochemically stained sections were analysed for cell numbers in the tumour area, infiltrative margin and distant liver stroma separately. These findings were correlated with clinical data and patient outcome. Results Tumour containment by a fibrotic capsule around liver metastases was observed in 37·8 per cent of 201 patients and was prognostic for improved survival (median (s.e.) survival 64 (6) and 31 (4) months for patients with capsule and no capsule respectively; P < 0·001) and independently led to higher R0 resection rates (P = 0·040). In multivariable analysis, CD45RO+ cell infiltration at the peritumoral margin with low CD45RO+ cell infiltration in the distant liver stroma (P = 0·001) and fibrotic capsule formation (P = 0·008) both independently prolonged patient survival. Using these two factors, a cellular immune score was designed and shown to stratify patient survival in test and validation samples (both P < 0·001). Conclusion Fibrotic capsule formation and localized cell infiltration of colorectal liver metastases by CD45RO+ cells were related to prolonged patient survival. Based on these immunological criteria a cellular immune score was developed to stratify patients according to prognosis.